2011
DOI: 10.1038/onc.2011.504
|View full text |Cite|
|
Sign up to set email alerts
|

The nuclear receptor TR3 regulates mTORC1 signaling in lung cancer cells expressing wild-type p53

Abstract: The orphan nuclear receptor TR3 (NR41A, Nur77) is overexpressed in most lung cancer patients and is a negative prognostic factor for patient survival. The function of TR3 was investigated in non-small cell lung cancer A549 and H460 cells, and knockdown of TR3 by RNA interference (siTR3) inhibited cancer cell growth and induced apoptosis. The prosurvival activity of TR3 was due, in part, to formation of a p300/TR3/Sp1 complex bound to GC-rich promoter regions of survivin and other Sp-regulated genes (mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
156
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(175 citation statements)
references
References 34 publications
17
156
0
Order By: Relevance
“…UV radiation activates the expression of Sesn1 and Sesn2 through p53 (10,14). p53-responsive elements were identified in the first exon and 9.6 kb downstream of the Sesn2 gene (29,30). These studies suggest that Sesn2 is a tumor suppressor.…”
Section: Discussionmentioning
confidence: 73%
“…UV radiation activates the expression of Sesn1 and Sesn2 through p53 (10,14). p53-responsive elements were identified in the first exon and 9.6 kb downstream of the Sesn2 gene (29,30). These studies suggest that Sesn2 is a tumor suppressor.…”
Section: Discussionmentioning
confidence: 73%
“…In a recent study, another TR3-dependent pro-oncogenic pathway was identified in NSCLC cells. Inactivated TR3 by either siTR3 or DIM-C-pPhOH, an inhibitor of TR3, both inhibited NSCLC cell growth and induced apoptosis (Lee et al, 2012). In p53 wildtype A549 and H460 cells, siTR3 or DIM-C-pPhOH respectively inhibited the mTORC1 pathway, and this was due to activation of p53 and induction of the p53-responsive gene sestrin 2, which subsequently activated the mTORC1 inhibitor AMPKα (mechanism 2) (Lee et al, 2012).…”
Section: Metabolism Related Proteinsmentioning
confidence: 99%
“…Inactivated TR3 by either siTR3 or DIM-C-pPhOH, an inhibitor of TR3, both inhibited NSCLC cell growth and induced apoptosis (Lee et al, 2012). In p53 wildtype A549 and H460 cells, siTR3 or DIM-C-pPhOH respectively inhibited the mTORC1 pathway, and this was due to activation of p53 and induction of the p53-responsive gene sestrin 2, which subsequently activated the mTORC1 inhibitor AMPKα (mechanism 2) (Lee et al, 2012). Thus, both siTR3 and DIM-C-pPhOH decreased or deactivated TR3, respectively, to inhibit growth and survival of NSCLC cells by inhibition of the mTORC1 pathway via p53/sestrin-dependent activation of AMPKα.…”
Section: Metabolism Related Proteinsmentioning
confidence: 99%
“…The mechanism underlying this anti-inflammatory activity in glia involved stabilization of nuclear corepressor proteins that prevented DNA binding of NF-kB at cis elements in the Nos2 promoter. Because C-DIM5 and C-DIM12 are activators in cancer cell lines of the NR4A family nuclear receptors Nur77 and Nurr1, respectively (Inamoto et al, 2008;Lee et al, 2010Lee et al, , 2012Li et al, 2012), they may exert neuroprotective effects by broadly suppressing NF-kB-dependent expression of inflammatory genes in glia, as suggested in recent studies characterizing the neuroprotective role of Nurr1 in PD, and warrants further study (Saijo et al, 2009). Examination of the three C-DIM compounds used in the present studies indicate that, although these compounds may have similar neuroprotective activities in vitro, the differing substituents on the aryl ring yield distinct pharmacokinetic profiles, which may in part be responsible for the differences in efficacy observed in vivo.…”
Section: Tablementioning
confidence: 99%